2006
DOI: 10.1590/s1677-04202006000300002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light and ethylene on endogenous hormones and development of Catasetum fimbriatum (Orchidaceae)

Abstract: This study attempted to clarify the effects of dark, light and ethylene on plant growth and endogenous levels of indole-3-acetic acid (IAA), cytokinins and abscisic acid in Catasetum fimbriatum. Dark-incubation fully inhibited root and pseudobulb formation as well as leaf growth, but favored shoot elongation. The results of continuous and active growth in dark-incubated shoots (stolons) were induced by strong apical meristem sink activity and by the significantly increased levels of cytokinins in shoots. In fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
2
13
0
6
Order By: Relevance
“…In view of this, the reduction in ABA concentration in response to darkness seems to be related to changes in the structure and/or function of chloroplasts. Researchers also agree that the exposure of plants to darkness increases the concentration of endogenous IAA, even twice (Liu et al 1996;Volmaro et al 1998;Suzuki and Kerbauy 2006), and it is in agreement with the results obtained for C. delgadii. The negative effect of the light on IAA concentration is presumably because light induces IAA-peroxidase and IAA-oxidase activity, the key enzymes involved in the breaking down of IAA (Liu et al 1996).…”
Section: Etiolation Resulting In Altered Concentration and Balance Ofsupporting
confidence: 76%
See 3 more Smart Citations
“…In view of this, the reduction in ABA concentration in response to darkness seems to be related to changes in the structure and/or function of chloroplasts. Researchers also agree that the exposure of plants to darkness increases the concentration of endogenous IAA, even twice (Liu et al 1996;Volmaro et al 1998;Suzuki and Kerbauy 2006), and it is in agreement with the results obtained for C. delgadii. The negative effect of the light on IAA concentration is presumably because light induces IAA-peroxidase and IAA-oxidase activity, the key enzymes involved in the breaking down of IAA (Liu et al 1996).…”
Section: Etiolation Resulting In Altered Concentration and Balance Ofsupporting
confidence: 76%
“…Dark treatment also greatly stimulates cytokinin accumulation. In shoots of dark-grown Catasetum fimbriatum, the total cytokinin concentration was almost threefold greater than in those growing under photoperiodic conditions (Suzuki and Kerbauy 2006). In stipe explants of C. delgadii, this difference reached more than 9 in favour of the dark.…”
Section: Etiolation Resulting In Altered Concentration and Balance Ofmentioning
confidence: 80%
See 2 more Smart Citations
“…In addition, it was shown that root tips isolated from Catasetum species are able to directly convert into buds, which in turn, give rise to new plants (Kerbauy 1984;Kraus and Monteiro 1989). Interestingly, previous evidence has also indicated that these events of morphogenesis described for Catasetum are affected by ethylene to some extent (Kerbauy and Colli 1997;Peres and others 1999;Suzuki and Kerbauy 2006). The above mentioned results suggest that modulation of ethylene concentration and/or signaling could be important for regulating some architectural traits in both shoot and root systems of Catasetum species; however, the influence of this hormone on the developmental plasticity of these plants is still unclear.…”
Section: Introductionmentioning
confidence: 96%